Perancangan Sistem Informasi Pelayanan Surat Pengantar Dukuh Berbasis Website “Dukuhku Online” - Lilik Arif Rahmadi; Paulus Tofan Rapiyanta; Diah Pradiatiningtyas - UBSI (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstract: Dukuh is a part of the Village Government that serves citizen's needs in the region. The current system that they used is still manual. It takes more time and a lot of money to get a cover letter from Dukuh with a manual system. The purpose of this research is to design a web-based service to request a cover letter from Dukuh. Data collection techniques used were observation, interview, literature study, and documentation. The system development method used a prototype method that is listening to the user request, making mock-up, and repairing mock-up. The results of the design system is a prototype design of cover letter service information web-based system